TERAPI BERBASIS SPIRITUALITAS DALAM PENANGANAN NYERI PASIEN KANKER PAYUDARA : A LITERATUR REVIEW - Risnah; Risdawati; Ani Auli Ilmi (Jurnal Midwifery, 2022)
Introduction Pain is the most common symptom in breast cancer patients. Pain felt in breast cancer patients is mild to severe pain that can be caused either from the part of the body affected by cancer or as a result of various types of therapy and the effects of breast treatment procedures including surgery and radiotherapy. Pain management alone, nowadays there is a lot of research evidence that the pharmacological approach combined with non-pharmacological therapy shows more significant results than only offering pharmacological therapy. Spirituality-based therapy is one of the non-pharmacological interventions that can be used to treat breast cancer. Method This study uses a quantitative descriptive research design with a literature review approach. The databases used include PubMed, Google Scholar, Spingerlink, and ProQuest. Result This study used 8 articles that matched the inclusion and exclusion criteria. From 8 articles, it shows that spirituality-based therapies that are effectively used in pain management are murottal therapy, prayer and dhikr Conclusion Murottal therapy, prayer, and dhikr are effective therapies used in pain management, besides that they can also be used to control anxiety and to regulate the emotions of breast cancer patients. Implications: The results of this study serve as a reference for nurses in providing non-pharmacological interventions to breast cancer patients who experience pain disorders. Thus, the independent function of nurses can be carried out properly